COVID-19 Pandemic and Overall Mental Health of Healthcare Professionals Globally: A Meta-Review of Systematic Reviews - Chutiyami, Muhammad; Cheong, Allen M. Y.; Salihu, Dauda; Bello, Umar Muhammad; Ndwiga, Dorothy; Maharaj, Reshin; Naidoo, Kogi; Kolo, Mustapha Adam; Jacob, Philomina; Chhina, Navjot; Ku, Tan Kan; Devar, Liza; et al. (Frontiers in Psychiatry, 2022)
Objective This meta-review aimed to provide a comprehensive overview of overall mental health of healthcare professionals during the COVID-19 pandemic. Method We conducted a comprehensive literature search on Academic Search Premier, CINAHL, Cochrane Library, and MEDLINE. A predefined eligibility criterion was used to screen the articles. The methodology quality of eligible studies was assessed using Joanna Briggs Institute checklist for systematic reviews. The data were narratively synthesised in line with the meta-review aim. Result Forty systematic reviews (represented as K=40), which reported data from 1,828 primary studies (N) and 3,245,768 participants met the inclusion criteria. The findings from a pooled prevalence indicate that anxiety (16%-41%, K=30, N=701), depression (14%-37%, K=28, N=584), and stress/post-traumatic stress disorder (18.6%-56.5%, K=24, N=327) were the most prevailing COVID-19 pandemic-related mental health conditions affecting healthcare workers. Other reported concerns included insomnia, burnout, fear, obsessive-compulsive disorder, somatization symptoms, phobia, substance abuse, and suicidal thoughts. Considering regions/countries, the highest anxiety was reported in the United-Kingdom (22.3%, 95% Confidence Interval [CI]:7-38, N=4) compared to other countries, while the highest depression was in the Middle-East, (41%, 95%CI:16-60, N=5) and stress in the Eastern Mediterranean region (61.6%, 95%CI:56.4-66.8, N=2) compared to other regions. The most significant risk factors include female gender, younger age, being a nurse, and frontline professional. The most-reported coping strategies include individual/group psychological support, family/relative support, training/orientation, and the adequacy of personal protective equipment. Conclusion It was concluded that healthcare professionals (nurses, doctors, allied health) have experienced various mental health issues during COVID-19 pandemic. The meta-review, therefore, recommends targeted interventions and health policies that address specific mental health issues to support health professionals worldwide during the duration of the COVID-19 pandemic and similar future health crises.